Effect of Ramipril on Urinary Protein Excretion in Maintenance Renal Transplant Patients Converted to Sirolimus. Issue 12 (14th July 2015) - Mandelbrot, D. A.; Alberú, J.; Barama, A.; Marder, B. A.; Silva, H. T.; Flechner, S. M.; Flynn, A.; Healy, C.; Li, H.; Tortorici, M. A.; Schulman, S. L.
Abstract : This prospective, randomized, double‐blind, placebo‐controlled study evaluated the effects of ramipril on urinary protein excretion in renal transplant patients treated with sirolimus following conversion from a calcineurin inhibitor. Patients received ramipril or placebo for up to 6 weeks before conversion and 52 weeks thereafter. Doses were increased if patients developed proteinuria (urinary protein/creatinine ratio ≥0.5); losartan was given as rescue therapy for persistent proteinuria. The primary end point was time to losartan initiation. Of 295 patients randomized, 264 met the criteria for sirolimus conversion (ramipril, 138; placebo, 126). At 52 weeks, the cumulative rate of losartan initiation was significantly lower with ramipril (6.2%) versus placebo (23.2%) (p < 0.001). No significant differences were observed between ramipril and placebo for change in glomerular filtration rate from baseline (p = 0.148) or in the number of patients with biopsy‐confirmed acute rejection (13 vs. 5, respectively; p = 0.073). One patient in the placebo group died due to cerebrovascular accident. Treatment‐emergent adverse events were consistent with the known safety profile of sirolimus and were not potentiated by ramipril co‐administration. Ramipril was effective in reducing the incidence of proteinuria for up to 1 year following conversion to sirolimus in maintenance renal transplant patients. Abstract : This randomized, double‐blind, placebo‐controlled study demonstrates that ramipril effectively prevents the development of proteinuria in renal transplant patients converted from a calcineurin inhibitor to sirolimus.